Antecedents of Return on Assets in Covid-19 Pandemic: Do LDR, CAR, OE and Bank Size Matters? - Hendra Sanjaya Kusno; Aldhea Shafitri; Endang Sri Apriani (Master of Accounting Universitas Trunojoyo Madura, 2022)
This study examines the effect of LDR, CAR, OE, and Bank Size on ROA. The population in this study, namely, Conventional Commercial Banks listed on the Indonesia Stock Exchange (IDX) for the 2020-2021 period amounted to 43 banks. The determination of the sample was carried out using the purposive sampling technique so that 62 research observations were obtained. The analysis used is multiple linear regression. The results showed that the LDR, CAR, and bank size have no effect, while OE have a significant negative effect on ROA. This research is expected to be an additional reference and information for subsequent researchers and academies in the field of accounting and investors during Covid-19 pandemic regarding investment decisions by considering the factors that affect ROA.